The New Deal was no deal - Smirna, Tudor Smirna (REVISTA PROCESOS DE MERCADO, 2010)
Currently, one of the loci communes of economic history is that the New Deal was the right cocktail of state-mandated policies to pull the US economy out of the Great Depression that begun in 1929. The relevance of this interpretation has increased tremendously since the crisis of 2008 that many compare with the crisis of 1929. There is a quasi-general demand for a new New Deal. This view is contended by the Austrian School of Economics and by other free-market oriented thinkers. They assert that only the free market offers the solutions necessary for economic recovery in any context, including the actual setting and the situation prevalent in the 1930s. This essay is intended as another attempt at a short revisionist history of the 1933-1939 period. Key words: Great Depression, New Deal, Roosevelt, Austrian School of Economics, economic history, revisionism. JEL Classification: E00, E32, N12, N22, N42. Resumen: En la actualidad, uno de los loci communes de la historia económica es que el New Deal fue el cóctel ideal de políticas ordenadas por el Estado para sacar a la economía de los EE.UU. de la Gran Depresión que comenzó en 1929. La relevancia de esta interpretación ha aumentado enormemente desde la crisis de 2008, que muchos comparan con la crisis de 1929. Existe una demanda casi general para un nuevo New Deal. Este punto de vista es debatido por la Escuela Austriaca de Economía y por otros pensadores liberales. Estos afirman que sólo el libre mercado ofrece las soluciones necesarias para la recuperación económica en cualquier contexto, incluido el actual y la situación prevaleciente en la década de 1930. El presente en-sayo pretende ser un nuevo intento de hacer una corta historia revisionista del período 1933-1939. Palabras clave: Gran Depresión, New Deal, Roosevelt, Escuela Austriaca de Economía, historia económica, revisionismo. Clasificación JEL: E00, E32, N12, N22, N42.